2018
DOI: 10.18520/cs/v115/i7/1297-1304
|View full text |Cite
|
Sign up to set email alerts
|

Lumen Anatomy and Localization of <i>Wolbachia</i> Sp. in the Thrips, <i>Plicothrips apicalis</i> (Bagnall)

Abstract: A detailed anatomical study of digestive system of insects has been done in some of the major insect orders such as Lepidoptera, Diptera, Coleoptera and Hemiptera. For other insects such as thrips, their emergence as an important agricultural pest has brought order Thysanoptera to focus. We describe the alimentary canal of Plicothrips apicalis (Bagnall) (Phlaeothripidae) and localize Wolbachia sp. in P. apicalis. The digestive tract of P. apicalis, a grass feeding species, is observed to be well demarcated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Another study by Kaczmarczyk et al [25] found that, in H. carpathicus, the Wolbachia genus was present in 70% of the pupae and in 56% of adults. Ambika and Rajagopal [72] also found that Wolbachia was associated with Plicothrips apicalis in the abdomen of their larvae and adults. Additionally, observations made in this study revealed a higher proportion of females relative to males in nature, particularly for Frankliniella, whereas, for S. hansoni, no males were collected in the field.…”
Section: Discussionmentioning
confidence: 88%
“…Another study by Kaczmarczyk et al [25] found that, in H. carpathicus, the Wolbachia genus was present in 70% of the pupae and in 56% of adults. Ambika and Rajagopal [72] also found that Wolbachia was associated with Plicothrips apicalis in the abdomen of their larvae and adults. Additionally, observations made in this study revealed a higher proportion of females relative to males in nature, particularly for Frankliniella, whereas, for S. hansoni, no males were collected in the field.…”
Section: Discussionmentioning
confidence: 88%